Measurement and Validation of Frailty as a Predictor of Outcomes in Women Undergoing Major Gynecological Surgery. Issue 12 (December 2015) - George, E. M.; Burke, W. M.; Hou, J. Y.; Tergas, A. I.; Chen, L.; Neugut, A. I.; Ananth, C. V.; Hershman, D. L.; Wright, J. D.
Abstract : ABSTRACT: Frailty has been defined as a medical syndrome characterized by loss of physical or mental reserve with diminished strength, endurance, and reduced physiologic function, often in the absence of a defined comorbidity. Frail individuals have increased vulnerability for developing increased dependency and/or death. Although frailty may be important in predicting surgical outcomes, it is unclear how best to measure frailty. Relatively few studies have examined the concept of frailty in patients undergoing gynecological surgery despite the potential association between frailty and adverse outcomes. There is widespread variation in the risk of adverse outcomes among patients with the same chronological age who undergo gynecological surgery. Several models have been proposed to measure aspects of frailty. A number of studies have demonstrated that routinely collected data can be used to calculate a modified frailty index (mFI). Increasing mFI is predictive of adverse surgical outcomes for procedures in general surgery, colorectal surgery, and vascular surgery. The use of the mFI in gynecological surgery is limited. The aim of this retrospective cohort study was to determine whether the mFI correlates with morbidity and mortality in women undergoing hysterectomy. The study was conducted at hospitals across the United States participating in the National Surgical Quality Improvement Program (NSQIP). Participants underwent hysterectomy for any indication from 2008 to 2012. Eleven variables in NSQIP were used to calculate the mFI. For each patient, the mFI ranged between 0.0 and 1.0; increasing mFI implies increased frailty. Model fit statistics (c-statistics) were used to assess the associations between mFI with morbidity and 30-day mortality. A c-statistic of 0.5 indicates that the model is no better than chance, whereas a c-statistic of unity indicates that the model perfectly predicts the outcome. The primary outcome measures were wound infection, severe complications, and mortality. Among 66, 105 patients identified, wound complications increased from 2.4% for patients with an mFI of 0 to 4.8% for those with mFI of 0.5 or greater ( P < 0.0001). Compared with patients with an mFI of 0, among those with an index of 0.5 or greater, severe complications increased from 0.98% to 7.3% ( P < 0.0001), overall complications rose from 3.7% to 14.5% ( P < 0.0001), and mortality increased from 0.06% to 3.2% ( P < 0.0001). Compared with chance alone, goodness-of-fit c-statistics showed that mFI increased the ability to detect wound complications by 11.4%, severe complications by 22.0%, and overall complications by 11.0%. These findings suggest that frailty is associated with adverse outcomes in women undergoing hysterectomy. Given that the mFI can be calculated from routinely collected clinical data, frailty may be useful in the preoperative risk assessment of women undergoing for hysterectomy and other major gynecological surgery.